Theoretical Aspects of Creating the Business Models for Supply Chain Process of Industrial Enterprises - Osipov, Victor A.; Astakhova, Ekaterina Vi. (International Journal of Supply Chain Management, 2018)
Abstract- Creating the business models for supply chain process is the subject of modern scientific research in the field of strategic planning and management of the enterprise. Some theoretical and practical aspects have not yet received a comprehensive scientific substantiation. General problem of enterprise management is traditionally analyzed in the researches, and business modeling is not fully investigated. The current state of the economy and peculiarities of its development, as well as the transformational nature of the Russian economy, show that the most important theoretical and practical aspects, which require scientific attention and development, analysis and systematization, are the theoretical provisions of business modeling concept for supply chain process; clarification of the term